TRANSFORMATION OF TAFSIR AT-TANWIR AUDIOVISUAL ON YOUTUBE IN THE VERSE OF UMMATAN WASATHA - Ramadhan, An Najmi Fikri (Universitas Muhammadiyah Surakarta, 2022)
Tafsir At-Tanwir Muhammadiyah began with its publication in Suara Muhammadiyah magazine. Then, Tafsir At-Tanwir was published by conducting an online interpretation study through the Youtube channel media which allowed the conversion of Tafsir At-Tanwir into an audiovisual interpretation. Even though the presenter refers to the interpretation, there will still be new arguments to support his explanation related to the surrounding reality. Given this background, the aim of this study is to compare the interpretation of At-Tanwir on Youtube and the original interpretation of Tafsir At-Tanwir in Suara Muhammadiyah magazine. This type of research is library research using a qualitative approach that is netnographic in nature by collecting data and information contained in the video recording of the Tafsir At-Tanwir recitation of Q.S Al-Baqarah verse 143 in the Youtube Tarjih channel media. After that, it was analyzed comparatively with the original Tafsir At-Tanwir original in Suara Muhammadiyah magazine to compare the interpretation of the ummatan wasatha>. The results in this study indicated that the interpretation of the ummatan wasatha> on Youtube was transformedor there were additional changes. The cause for this is due to the context of the reality around presenter and the factors of audience participants following in the online Tafsir At-Tanwir recitation.